Barred: Labor Market Dynamics and Human Capital Development among People on Probation and Parole. Issue 1 (May 2022) - Sykes, Bryan L.; Ballard, Meghan; Kaiser, Daniela; Mata, Vicente Celestino; Sharry, J. Amanda; Sola, Justin
Obtaining employment is a major barrier to social reintegration for people on probation or parole. Research on the reentry process identifies several mechanisms that accentuate difficulties in locating work, including human capital development, structural changes in the labor market, and onerous probation and parole conditions. In this article, we review theories that explain low labor market participation rates among people reentering society, and we draw on multiple sources of data to identify the types of jobs that are available to people with low human capital. We find that nearly a quarter of people in America's state and federal prisons had permanently removed themselves from the formal labor market before their most recent arrest; however, exclusionary hiring practices in the formal labor market often push those carrying the stigma of a criminal record into underground or informal labor markets, where wage rates are markedly higher than the federal minimum wage. Our findings demonstrate that severe and chronic employment struggles often predate and follow incarceration. We provide a detailed discussion of policy reform proposals that could help to remedy this harmful dynamic.